Optimizing the Role of Traders Collector in Expanding Vegetable Market Access Local Organic in Wamena Papua Mountains - Herlyani, Herlyani S.; Astaman, Putra (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Collecting traders in Wamena play a crucial role in enhancing farmers' welfare. This study explores how these traders can boost the availability of organic vegetables while adapting to local conditions. The research identifies challenges, opportunities, and best practices specific to Wamena, using a qualitative approach with in-depth interviews and participatory observations of farmers and collectors. Collecting traders act as a key link between rural farmers and urban consumers, directly collecting harvests from fields. They also manage post-harvest tasks such as sorting, classifying, and packaging to ensure quality. However, several obstacles hinder their full potential. Limited infrastructure, such as poor road access, presents a significant challenge, as does the lack of capital for buying large quantities and maintaining stock. The use of traditional measurement units like tokens leads to inaccurate weight estimates, disadvantaging both farmers and traders. Additionally, high shipping costs burden traders and reduce their profit margins. To optimize the role of collecting traders, improvements in service quality, market network expansion, and vegetable distribution are needed. Addressing these challenges will help enhance the welfare of farmers, ensure the availability of quality organic vegetables, and meet consumer demand in Wamena. Improving distribution methods for organic vegetables is essential to support this goal.